Rope Burn - Johnstone, William W; Johnstone, J. A (Johnstone, William W. Those Jensen boys! (Series), 2020)
"Those Jensen boys, Ace and Chance, find themselves on the wrong side of the law--and the raw end of justice--inside the meanest, dirtiest prison in the Arizona territory" --back cover.